Lower and Upper Bounds of Fractional Metric Dimension of Connected Networks - Javaid, Muhammad; Aslam, Muhammad Kamran; Asjad, Muhammad Imran; Almutairi, Bander N.; İnç, Mustafa; Almohsen, Bandar (Mdpi, 2021)
The distance centric parameter in the theory of networks called by metric dimension plays a vital role in encountering the distance-related problems for the monitoring of the large-scale networks in the various fields of chemistry and computer science such as navigation, image processing, pattern recognition, integer programming, optimal transportation models and drugs discovery. In particular, it is used to find the locations of robots with respect to shortest distance among the destinations, minimum consumption of time, lesser number of the utilized nodes, and to characterize the chemical compounds, having unique presentations in molecular networks. After the arrival of its weighted version, known as fractional metric dimension, the rectification of distance-related problems in the aforementioned fields has revived to a great extent. In this article, we compute fractional as well as local fractional metric dimensions of web-related networks called by subdivided QCL, 2-faced web, 3-faced web, and antiprism web networks. Moreover, we analyse their final results using 2D and 3D plots.
Keywords: fractional metric dimension; web-related networks; resolving neighbourhoods